Situation Report: Romania, 3 February 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Soviet-Romanian Industrial Cooperation and Trade / by Vladimir Socor An Underground Essay on Urban and Rural Redevelopment / by Dan Ionescu Back to Literary Show Trials / by Carmen Pompey New Moves to Boost the Birthrate / by Paul Gafton El Greco and the Rain in Romania / by Dan Ionescu